Psychotic, acritical and precarious? A Lacanian exploration of the neoliberal consumer subject. (September 2019) - Lambert, Aliette
Extending the critical project of interrogating the consumer subject form, in this study, the consumer subject is read as potentially acritical, precarious and psychotic through Dufour's Lacanian-inspired analysis of neoliberal subjectivity. Reflecting on two case studies from an ethnographic-type study of young women, identity and consumer culture, I demonstrate how participants attempt to fulfil neoliberal ideals related to agency, productivity and creativity. Relying on commodities for symbolic anchoring in doing so, a 'psychotic' and precarious subject position is evidenced. While the findings could certainly be interpreted as productive, tendencies toward materialism, uncertainty and anxiety, along with pervasive mental health issues, provided the impetus to further problematise dominant understandings of the consumer. Neoliberal consumer culture is evidenced as a harmful, dehumanising ideology that fosters competitiveness, individuality and meritocratic tendencies, encouraging a reliance on ever-changing, transient commodities to (in)form the self. This occurs at the expense of compromise, communality and social welfare, through which subjects may find more stable and emancipatory symbolic anchors. Only by recognising critical theorisations of the consumer as dominant subject positions of neoliberalism can cultural consumer researchers begin to imagine opportunities for resistance and emancipatory change.